195 Association between pet ownership and sleep in the Swedish CArdioPulmonary bioImage Study (SCAPIS). (3rd May 2021) - van Egmond, Lieve; Titova, Olga E; Lindberg, Eva; Fall, Tove; Benedict, Christian
Abstract: Introduction: Preliminary findings suggest that pets may improve the owner's sleep via companionship, security, physical activity, and relaxation. On the other hand, pets can disrupt the owner's sleep. Due to the heterogeneity of the results and the low number of studies in this field, more studies with a bigger sample size are needed to explore this association. Methods: Using data from the Swedish CArdioPulmonary bIoimage Study (SCAPIS) cohort, we investigated the association of pet ownership with the following self-reported sleep outcomes in 3, 788 to 4, 574 participants using regression modeling: achieving the recommended daily sleep duration for adults (i.e., at least 7 hours per day); sleep quality as measured by the Pittsburgh Sleep Quality Index (a score of >5 indicating poor sleep quality); and difficulty falling or staying asleep. Results: Sleep metrics were not associated with pet ownership, dog ownership, and dog walking when controlling for possible confounders. In contrast, cat ownership was associated with a higher odds ratio of failing to achieve the recommended duration of 7 hours of sleep per day (1.18 [1.02, 1.37] vs. non-cat owners). This association persisted even after adjusting for various factors known to affect sleep (e.g., shift work, lack of social interaction, and chronic stress). Conclusion: We found that owning a cat was associated with increased odds of sleeping less than the recommended seven hours per day. General pet ownership and dog ownership were not associated with either of the sleep outcomes. Whether this means that cats represent a risk factor for short sleep duration cannot be derived from the present observational study. Future studies should more thoroughly investigate the various aspects of cat ownership, e.g., the cat′s breed, age, and co-sleeping with the cat. Support (if any):